Safety and Health Status of Educational and Research Laboratories of Shiraz University of Medical Sciences based on ELMERI Approach - Mahdi Malakoutikhah; Hadise Korouni; Mehdi Jahangiri (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Observation of the safety principles in educational and research laboratories is very important to protect the researchers and students. This study was conducted to investigate the safety and health status of the educational and research laboratories in Shiraz University of Medical Sciences. Methods: This cross-sectional study was conducted in 34 educational and research laboratories of Shiraz University of Medical Sciences in 2013. In this regard, the safety and health status of the studied laboratories was studied based on the ELMERI Indicator. This indicator consists of 59 items in nine dimensions including electrical safety, fire safety, building safety, emergency response management, chemical safety, individual safety, device and equipment safety, waste management, and safety management. Finally, the Laboratory Safety Index (LSI) was calculated in percentage using the mean and standard deviation by SPSS 16 in each laboratory. Results: The mean of LSI was 77.62 ± 10.35 percent in all the studied laboratories. The highest and the lowest percentages of LSI score were in individual safety (89.46 ± 12.86%) and emergency response management (53.72 ± 35.46%) dimensions, respectively. The other dimensions were classified to have good status. Conclusion: According to the results, the overall status of safety and health was good in the studied laboratories. However, in the dimension of emergency response management, the status of laboratories was unacceptable. So, required measures should be taken in this regard. For example, all the emergency exit systems should be investigated, instructions should be issued, staffs should be trained with regard to the emergency conditions, emergency exit doors should be designed, and the requirements for the exit emergency routes should be observed appropriate to the laboratory conditions.